Effect of mirabegron on tight junction molecules in primary cultured rat Sertoli cells. (31st January 2019) - Tanaka, Mikito; Chiba, Koji; Okada, Keisuke; Fujisawa, Masato
Abstract: Mirabegron is a selective beta3‐adrenoceptor (β3 ‐AR) agonist, which is commonly used for the treatment of overactive bladder. This medicine is associated with atrophy of reproductive organs in rats. However, no study has examined the detailed action and mechanism of its toxicity in reproductive cells. In this study, we examined the effect of mirabegron on primary cultured rat Sertoli cells. Firstly, RT‐PCR and immunocytochemistry revealed that β3 ‐AR was present in rat Sertoli cells. Then, primary cultured rat Sertoli cells were treated with mirabegron. Quantitative real‐time PCR revealed that mirabegron treatment induced a significant increase in claudin‐11 mRNA, which is crucial for spermatogenesis. Western blot analysis also showed that mirabegron treatment significantly activated p44/42 mitogen‐activated protein kinase (MAPK). After additional treatment with U0126, a specific noncompetitive inhibitor of mitogen‐activated protein kinase kinase (MAPKK), the upregulation of claudin‐11 mRNA induced by mirabegron was reduced. At the same time, immunocytochemistry showed mirabegron treatment disturbed claudin‐11 localisation to tight junction, which was recovered when treated with mirabegron in the presence of U0126. These results suggest that mirabegron treatment is associated with assembly of the blood–testis barrier through p44/42 MAPK pathway. These findings could explain one of the underlying mechanisms of reproductive toxicity induced by mirabegron.